INOVASI MESIN-MESIN TEKNOLOGI PASCAPANEN KOPI SEBAGAI PRODUK USAHA INTELEKTUAL KAMPUS POLITEKNIK NEGERI LHOKSEUMAWE - Indra Mawardi; Nurdin Nurdin; Zulkarnaini Zulkarnaini (Panrita Abdi - Jurnal Pengabdian pada Masyarakat, 2020)
Innovation of Coffee Postharvest Technology Machines as Campus Intellectual Business Products Lhokseumawe State PolytechnicAbstract. The growth of the area of coffee plantations continues to increase every year needs to be supported by the readiness of postharvest technology that is suitable to be able to produce quality coffee beans. The Lhokseumawe State Polytechnic has taken the opportunity to form a business unit for the production of appropriate the technology of the postharvest coffee machine, through a service program with the scheme of the Campus Intellectual Product Business Development Program. The center for production of machinery for appropriate technology for postharvest coffee The Lhokseumawe State Polytechnic aims to increase the productivity of coffee farmers through the mechanization of the coffee postharvest process by innovating appropriate technology technologies for coffee postharvest. Besides that to support campus independence through the business of producing coffee postharvest machines. The method of implementing activities starts from machine design, provision of raw materials, production processes, to product marketing. From the results of the activity has been formed production centers of appropriate technology for postharvest coffee machines. The center for production of machinery appropriate technology postharvest coffee has made innovations in coffee postharvest technology machines. Innovative products from the machine production center for appropriate technology for postharvest coffee include mobile pulper machines, coffee bean washing machines, mobile huller machines and multi-functional hullers, coffee bean sorting machines, and vibrating systems. These machines have advantages of construction and mobilization compared to products that have been circulating in the market so far. Product marketing has been done through a showroom as a place to showcase products, sales websites, and online stores.Keywords: innovation, postharvest technology, coffee, campus intellectual products.Abstrak. Pertumbuhan luas perkebunan kopi terus meningkat setiap tahun perlu didukung dengan kesiapan teknologi pascapanen yang cocok untuk dapat menghasilkan biji kopi bermutu. Politeknik Negeri Lhokseumawe telah mengambil peluang tersebut dengan membentuk unit usaha teknologi tepat guna pascapanen kopi, melalui program pengabdian dengan skim Program Pengembangan Usaha Produk Intelektual Kampus (PPUPIK). Kegiatan PPUPIK ini bertujuan menunjang kemandirian kampus melalui usaha produksi mesin-mesin pascapanen kopi melalui inovasi dan produksi mesin-mesin TTG pascapanen kopi. Kegiatan ini pada akhirnya akan meningkatkan produktifitas petani kopi melalui mekanisasi proses pascapanen kopi yang baik. Metode kegiatan PPUPIK  terbagi dalam tiga tahapan, yaitu tahapan produksi, pemasaran dan pendirian unit usaha. Tahapan produksi  dimulai dari design mesin, penyediaan bahan baku, proses produksi, sampai pemasaran produk. Dari hasil kegiatan telah terbentuk unit usaha Pusat Produksi Mesin-mesin Teknologi Tepat Guna Pascapanen Kopi. Unit usaha ini telah melakukan inovasi mesin teknologi pascapanen kopi. Produk inovasi dari Pusat Produksi Mesin-mesin Teknologi Tepat Guna Pascapanen Kopi antara lain mesin pulper mobile, mesin pencuci biji kopi, mesin huller mobile dan huller multi fungsi, dan mesin sortasi biji kopi sistem getar. Mesin-mesin TTG tersebut mempunyai keunggulan dari konstruksi dan mobilisasi dibandingkan produk yang telah beredar dipasaran selama ini. Pemasaran produk telah dilakukan melalui showroom sebagai tempat lokasi pamer produk, website penjualan, dan toko online.Kata kunci:  inovasi, teknologi pascapanen, kopi, produk intelektual kampus.